The Influence of Brand Image, Awareness and Customer Satisfaction in Increasing Loaylity And Choosing Islamic Banking In Indonesia - Syaifuddin; Andrie Yuswanto; Ahmad hariri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The growth of Islamic banks in Indonesia is still far from what is expected, where Indonesia is a country with a Muslim majority population and the largest in the world. However, Islamic banks are only able to get 6% of the market share compared to conventional banks. The purpose of this study is to find out how significant the influence of Brand Image and Awareness factors and customer satisfaction in increasing customer loyalty and the desire to use Islamic banking in Indonesia is. This research was conducted using an online survey to the public using the accident sampling technique. This questionnaire uses a modified Likert scale technique. From the distribution carried out, 493 respondents who filled out questionnaires were collected from 1500 respondents. After the analysis, it was found that. Service Quality has a positive effect on Customer Satisfaction, while Brand Image has a negative effect on Customer Satisfaction, for Customer Satisfaction it has a positive effect on Customer Loyalty and Customer Satisfaction has a positive effect on Purchase Intention. But Awareness has a negative effect on Purchase Intention. For Customer Loyalty has a positive effect on Purchase Intention. The findings from this study are very useful for players in the Islamic banking industry to see how they can increase the market share and progress of Islamic banks in Indonesia